Synthesis and pharmacological evaluation of fluorinated benzo[7]annulen‐7‐amines as GluN2B‐selective NMDA receptor antagonists. (11th July 2019) - Thum, Simone; Schepmann, Dirk; Reinoso, Raquel F.; Alvarez, Inés; Ametamey, Simon M.; Wünsch, Bernhard
Abstract : Because of their neuroprotective potential, GluN2B‐selective ligands are of great interest for the treatment of various neurological and neurodegenerative disorders. Fluorinated benzo[7]annulen‐7‐amines, capable for PET, were synthesized by combining fluorinated phenylalkylamines with differently substituted ketones. Relationships between substitution pattern and GluN2B affinity as well as selectivity towards σ1 and σ2 receptors were investigated. Two promising ligands (18a and20c ) were selected for further pharmacological evaluation. Besides a slight serotonin transporter (SERT), norepinephrine transporter (NET), and hERG affinity, they did not show interaction with other targets. Furthermore, the p K a value of a set fluorinated ligands, bearing the fluorine atom in different positions, was determined. Abstract : In order to image GluN2B subunit containing NMDA receptors by PET, a series of tetrahydro‐3‐benzazepines bearing an F‐atom in the phenylalkyl side chain has been synthesized. Relationships between the structure in particular the position of the F‐atom in the side chain and the GluN2B affinity, selectivity, and basicity were identified.